The Cultural Authenticity Of Visual Narratives In Children’S Picture Books In China - Qi, Fenfen (2024)
This study was inspired by an analysis of the Chinese picture book market, where imported foreign picture books account for more than 80% of children's picture book sales in China. Extensive exposure to a foreign culture is detrimental to developing national identity and a sense of belonging in young children. As a result, original Chinese picture books must incorporate traditional Chinese artistic language, national characteristics, and aesthetic guidelines. As a starting point, the research sample was consist of children's picture books that express traditional Chinese art styles. In order to analyse the visual narrative images of the selected samples, this study used qualitative analysis to code the samples by using multimodal discourse analysis as a model framework, and the findings were validated using interviews. The expression of cultural authenticity in picture books in narrative form was an essential instrument for children's exposure to culture and a source of overt and covert 'ideological' information about the world and social values. Therefore, this study examined the visual elements of traditional genre picture book images, beginning with the internal structure of picture books. Besides that, this research also focused on the visual narrative expression of visual communication guidelines regarding the constitutive laws of images within picture books. Finally, this study aimed to develop a visual narrative model for children's picture books in traditional Chinese genres that authentically represent classic art and culture.